Vanadium oxide‐supported copper ferrite nanoparticles: A reusable and highly efficient catalyst for rhodamine B degradation via activation of peroxymonosulfate. (27th July 2021) - Salami, Rasoul; Amini, Mojtaba; Bagherzadeh, Mojtaba; Chae, Keun Hwa
Abstract: A magnetic vanadium oxide nanoparticles supported on spinel copper ferrite (CuFe2 O4 –VOx ) are prepared, characterized, and examined for the peroxymonosulfate (PMS) activation to degrade Rhodamine B (RhB) in water solution. Interestingly, the results show that despite the inability of mixture of copper ferrite and vanadium oxides nanoparticles to the effective RhB decomposition, the prepared catalyst exhibits an excellent catalytic ability toward RhB oxidation. The influence of vital parameters, such as temperature, PMS concentration, catalyst loading, and initial pH are discussed comprehensively. The kinetic studies demonstrate that the pseudo‐first‐order model is well fitted for RhB degradation in CuFe2 O4 –VOx /PMS system and the activation energy is estimated at 19.60 kJ mol −1 . Furthermore, it is found out that the concentration of leached metal ions in solution is negligible and PMS activation is done mainly on the surface of the catalyst. A probable mechanism of PMS activation over RhB degradation is proposed based on the results of free radical quenching studies and X‐ray photoelectron spectroscopy (XPS) analysis. Radical quenching experiments using various scavengers suggest SO4 − as a main reactive species in the degradation. Abstract : Vanadium oxide nanoparticles supported on copper ferrite were synthesized and found out to be highly efficient and recyclable catalyst for PMS activation toward RhB degradation.